Functional Limb Restoration Through Amputation: Minimizing Pain and Optimizing Function With the Use of Advanced Amputation Techniques. Issue 3 (23rd March 2021) - Souza, Jason M.; Wade, Sean M.; Harrington, Colin J.; Potter, Benjamin K.
Abstract : Objective: To demonstrate the role of advanced orthoplastic techniques in harnessing the full potential of elective amputation as a functionally restorative procedure. Summary of Background Data: Once considered the unfortunate consequence of failed reconstructive efforts, recent outcomes studies have prompted a re-evaluation of the role of amputation in the management of complex extremity trauma. However, even as amputation is appropriately afforded greater consideration as part of the reconstructive algorithm, reconstructive techniques that are commonly utilized in pursuit of limb salvage are rarely applied to amputation. Methods: The following case demonstrates the successful application of orthoplastic reconstructive techniques to achieve optimal pain and functional outcomes in a 41-year-old active duty soldier who underwent an elective transtibial amputation after prolonged, limb salvage. Results: The patient presented with a large osteocutaneous proximal tibial defect secondary to trauma and subsequent osteomyelitis. The patient underwent a free scapular-parascapular fasciocutaneous flap to provide soft tissue coverage and facilitate the skeletal reconstruction necessary for either continued limb salvage or amputation. Due to tibial allodynia and severely limited ankle function, the patient subsequently elected for amputation in favor of continued limb salvage. Thus, a transtibial amputation was performed concurrently with a pedicled vascularized fibula to address the proximal tibial defect. A modified agonist-antagonist myoneural interface procedure was used to maximize post-amputation function, with creation of regenerative peripheral nerve interface constructs to prophylax against neurogenic pain. After the operation, the patient achieved improved function of the extremity with the use of a prosthesis and reported substantially improved pain while remaining on active duty in a warfighting military occupational specialty. Conclusions: By addressing all of the reconstructive components commonly considered in limb salvage, an orthoplastic approach to amputation surgery can minimize pain and maximize the rehabilitative potential of the amputee.